2023
DOI: 10.1021/acsestengg.3c00190
|View full text |Cite
|
Sign up to set email alerts
|

Natural Pyrite-assisted Mechanochemical Recovery of Insoluble Manganese from Electrolytic Manganese Residue: Kinetics and Mechanisms

Hongrui Xiang,
Zhihui Yang,
Size Liu
et al.

Abstract: Numerous traditional methods have been applied to extracting manganese from electrolytic manganese residue (EMR). However, most of them focused on the recovery of water-soluble manganese from EMR, while insoluble manganese, whose content is usually high in EMR, was generally ignored. Herein, the recovery of insoluble manganese in EMR was systematically investigated by a natural pyrite-assisted mechanochemical method. The recovery efficiency of insoluble manganese exceeded 86%, and the leaching efficiency of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…A new characteristic peak was observed at 35.22°, which may be attributed to β-FeCr 2 O 4 . , These results indicated that Fe 3+ attaches to the surface and pore structure of biochar, providing more adsorption sites, which was beneficial for the adsorption of a large number of pollutants. Moreover, the results indicated that a series of chemical reactions may have occurred between Fe and Cr­(VI) on Fe@MBC during the progress of the removal reaction. , …”
Section: Results and Discussionmentioning
confidence: 93%
“…A new characteristic peak was observed at 35.22°, which may be attributed to β-FeCr 2 O 4 . , These results indicated that Fe 3+ attaches to the surface and pore structure of biochar, providing more adsorption sites, which was beneficial for the adsorption of a large number of pollutants. Moreover, the results indicated that a series of chemical reactions may have occurred between Fe and Cr­(VI) on Fe@MBC during the progress of the removal reaction. , …”
Section: Results and Discussionmentioning
confidence: 93%
“…However, there is still ammonia nitrogen in the electrolyte that has not been removed, and so, it is necessary to further study how to treat it synchronously. In addition, the recovery of insoluble manganese from electrolytic manganese slag is also worth exploring [18], so as to realize harmless treatment and resource utilization in the real sense.…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, tremendous progress has been made to eliminate heavy metals from water. Some low-cost advantage-oriented approaches (i.e., chemical precipitation, ion flotation, ion exchange, adsorption, and coagulation/flocculation) have been used to remove heavy metals from wastewater. Among these approaches, adsorption is considered suitable for dealing with wastewater containing low concentrations of metal ions . Adsorbents such as activated carbon, mesoporous resins, and membranes have been reported for removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%